Sistem Pertahanan Jepang pada Perang Dunia II di Kawasan Hutan Lindung Pananjung, Pangandaran - Octaviadi Abrianto (Badan Riset dan Inovasi Nasional (BRIN), 2022)
Indonesian territories were under Japanese occupation from 1943 until 1945, during that time, the Japanese forces were built numbers of defenses building and fort around strategic and important areas in Indonesia, one of them is in Pananjung Natural Reserve in Pangandaran, West Java. This paper will discuss the defense system and the design of these defenses buildings at the area through exploration and description of the buildings. Pananjung defense system has concentric design with the first line of defense located at the bottom of the hill and gradually going up to the top. Each of this defense system had clear view of one and another so they have an overlapping kill zone to work together. The design of the defense buildings also incorporated local resources to make an efficient defense.